Identification of glucose‐6‐phosphate transporter as a key regulator functioning at the autophagy initiation step. Issue 16 (15th May 2015) - Ahn, Hye-Hyun; Oh, Yumin; Lee, Huikyong; Lee, WonJae; Chang, Jae-Woong; Pyo, Ha-Kyung; Nah, Do hyung; Jung, Yong-Keun
Abstract : Autophagy is a catabolic process involving autophagosome formation via lysosome. However, the initiation step of autophagy is largely unknown. We found an interaction between ULK1 and ATG9 in mammalian cells and utilized the interaction to identify novel regulators of autophagy upstream of ULK1. We established a cell‐based screening assay employing bimolecular fluorescence complementation. By performing gain‐of‐function screening, we identified G6PT as an autophagy activator. G6PT enhanced the interaction between N‐terminal Venus‐tagged ULK1 and C‐terminal Venus‐tagged ATG9, and increased autophagic flux independent of its transport activity. G6PT negatively regulated mTORC1 activity, demonstrating that G6PT functions upstream of mTORC1 in stimulating autophagy. Abstract : ULK1 interacts with ATG9 in mammalian cells. ULK1‐VN/ATG9‐VC BiFC assay isolated a new autophagy modulator. G6PT regulates autophagic flux independent of its enzyme activity. G6PT negatively regulates mTORC1 activity.